Effect of antidiabetic treatment on bone - Jackuliak, P; Kužma, M; Payer, J (Physiological research, 2019)
Patients with diabetes mellitus are at an increased risk of bone fractures. Several groups of effective antidiabetic drugs are available, which are very often given in combination. The effects of these medications on bone metabolism and fracture risk must not be neglected. Commonly used antidiabetic drugs might have a positive, neutral or negative impact on skeletal health. Increased risk of fracture has been identified with use of thiazolidinediones, most definitively in women. Also treatment with sulfonylureas can have adverse effects on bone. One consequence of these findings has been greater attention to fracture outcomes in trails of new diabetes medication (incretins and SGLT-2 inhibitors). The effect of insulin on bone is discussed and the risk of fractures in patients using insulin seems to be unrelated to insulin as itself. The aim of the review is to summarize effects of antidiabetic treatment on bone - bone mineral density, fractures and bone turnover markers. The authors also try to recommend a strategy how to treat patients with diabetes mellitus regarding the risk of osteoporotic fractures. In this review the problem of how to treat osteoporosis in patient with diabetes is also discussed.
Keywords: inhibitory kostní resorpce; Bone Density Conservation Agents; Humans; metformin; sulfonylmočovinové sloučeniny; osteoporóza; Incretins; Metformin; Bone and Bones; Sulfonylurea Compounds; kosti a kostní tkáň; lidé; zvířata; Diabetes Mellitus, Type 2; Hypoglycemic Agents; Insulin; Thiazolidinediones; inkretiny; hypoglykemika; thiazolidindiony; Animals; Osteoporosis; diabetes mellitus 2. typu; inzulin